Good girls, bad girls of the New Testament: their enduring lessons - Wray, T. J. (Rowman & Littlefield, 2016)
Life for women during New Testament times -- Sisters, sinners, and supporters -- Sister friends: Martha and Mary of Bethany -- Suspicious sisters: Bernice and Drusilla, the great-granddaughters of Herod the Great -- Caught in the act: the adulterous woman in John's gospel -- Blood guilt: the woman with a twelve-year hemorrhage -- A woman of substance: Mary Magdalene -- Widow's rising: Tabitha, a loving benefactor -- Mothers, murderers, and missionaries -- Angelic gift: Elizabeth, Mother of John the Baptist -- Jesus' mom: Mary of Nazareth -- Off with his head! Herodias and the beheading of John the Baptist -- I had a dream: the wife of Pontius Pilate -- Spreading the good news: Prisca, a missionary of Paul -- A conversation with Jesus: the woman at the well -- Concluding thoughts